2014
DOI: 10.3390/md12073953
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Heparin by Cationically Modified Chitosan

Abstract: This study was performed to evaluate the ability of N-(2-hydroxypropyl)-3-trimethylammonium chitosan chloride (HTCC), the cationically modified chitosan, to form biologically inactive complexes with unfractionated heparin and thereby blocking its anticoagulant activity. Experiments were carried out in rats in vivo and in vitro using the activated partial thromboplastin time (APTT) and prothrombin time (PT) tests for evaluation of heparin anticoagulant activity. For the first time we have found that HTCC effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
2
9
0
Order By: Relevance
“…41 Limited cell infiltration often delays and even prevents the regeneration and remodeling progress of vascular grafts in the latter term. 28 In the present study, benefiting from the surface heparinization of PCL through H 2 N–PEG–NH 2 featured by a hierarchical double electrospun microfiber structure, and increased hydrophilicity and biodegradation rate, CCK8 assay clearly revealed that the surface heparinized electrospun PCL vascular scaffolds indeed supported the adhesion and proliferation of ECs and SMCs. As discussed above, the surface heparinization endowed the grafts with improved hydrophilicity as well as the significantly modified morphology.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…41 Limited cell infiltration often delays and even prevents the regeneration and remodeling progress of vascular grafts in the latter term. 28 In the present study, benefiting from the surface heparinization of PCL through H 2 N–PEG–NH 2 featured by a hierarchical double electrospun microfiber structure, and increased hydrophilicity and biodegradation rate, CCK8 assay clearly revealed that the surface heparinized electrospun PCL vascular scaffolds indeed supported the adhesion and proliferation of ECs and SMCs. As discussed above, the surface heparinization endowed the grafts with improved hydrophilicity as well as the significantly modified morphology.…”
Section: Discussionsupporting
confidence: 57%
“…20 Heparin is a natural anticoagulant substance and has a long safe history for use in the thromboembolic diseases, myocardial infarction, cardiovascular surgery, cardiopulmonary bypass, cardiac catheterization, hemodialysis access for end-stage renal disease, and so on. [26][27][28] Heparin molecule contains many anionic groups, such as sulfonic acid group (-SO 3 H) and carboxyl group (-COOH), so it is a natural hydrophilic polysaccharide having strong negative electricity. 29 This structural feature enables it holding great promise to enhance vascular TE through its ability to prevent vascular clogging and adsorb growth factor and other peptide molecules to realize cell adhesion and proliferation through electrostatic interaction substantially facilitating endothelialization and regulate proliferation and differentiation of SMCs ultimately.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, HTCC forms smaller aggregates with heparin and with less polydispersity, which can be advantageous in medical procedures, such as intravenous applications. Lorkowska-Zawicka et al [163] evaluated the aforementioned results with applications in rats in vivo and in rats' blood in vitro, and observed that the reversal action of heparin is maintained under the conditions evaluated, safely and without toxic effects when administered in doses adjusted for complexation with heparin.…”
Section: Applications Of Htcc and Similar Compoundsmentioning
confidence: 99%
“…In addition, the polymer was rapidly eliminated (half-life of 12.5 ± 3.0 minutes) without any blood and organ toxicity. 37 The polymeric backbone of antidotes can also be fully synthetic, such as in PAH (poly(allylamine hydrochloride)). Directly inspired by protamine, a PAH polymer on which 9% of the amino groups were replaced by arginine was tested as heparin antagonist.…”
Section: Polymeric/dendritic Bindersmentioning
confidence: 99%